Effects of Combined Treatment with Ionizing Radiation and the PARP Inhibitor Olaparib in BRCA Mutant and Wild Type Patient-Derived Pancreatic Cancer Xenografts - Lohse, Ines (PLoS One, 2016)
BACKGROUND: The BRCA2 gene product plays an important role in DNA double strand break repair. Therefore, we asked whether radiation sensitivity of pancreatic cancers developing in individuals with germline BRCA2 mutations can be enhanced by agents that inhibit poly (ADP-ribose) polymerase (PARP). METHODS: We compared the sensitivity of two patient-derived pancreatic cancer xenografts, expressing a truncated or wild type BRCA 2, to ionizing radiation alone or in combination with olaparib (AZD-2281). Animals were treated with either a single dose of 12Gy, 7 days of olaparib or 7 days of olaparib followed by a single dose of 12Gy. Response was assessed by tumour growth delay and the activation of damage response pathways. RESULTS: The BRCA2 mutated and wild type tumours showed similar radiation sensitivity, and treatment with olaparib did not further sensitize either model when compared to IR alone. CONCLUSIONS: While PARP inhibition has been shown to be effective in BRCA-mutated breast and ovarian cancers, it is less well established in pancreatic cancer patients. Our results show no radiosensitization in a germline BRCA 2 mutant and suggest that combining PARP inhibition and IR may not be beneficial in BRCA 2 related pancreatic tumors.